Harnessing the Potential of Killers and Altruists within the Microbial Community: A Possible Alternative to Antibiotic Therapy? - Larisa N. Ikryannikova; Leonid K. Kurbatov; Surinder M. Soond; Andrey A. Zamyatnin (MDPI AG, 2019)
In the context of a post-antibiotic era, the phenomenon of microbial allolysis, which is defined as the partial killing of bacterial population induced by other cells of the same species, may take on greater significance. This phenomenon was revealed in some bacterial species such as Streptococcus pneumoniae and Bacillus subtilis, and has been suspected to occur in some other species or genera, such as enterococci. The mechanisms of this phenomenon, as well as its role in the life of microbial populations still form part of ongoing research. Herein, we describe recent developments in allolysis in the context of its practical benefits as a form of cell death that may give rise to developing new strategies for manipulating the life and death of bacterial communities. We highlight how such findings may be viewed with importance and potential within the fields of medicine, biotechnology, and pharmacology.